Engineering strategies for chitin nanofibers - Zhang, Xiaolin; Rolandi, Marco (Journal of materials chemistry. B, Materials for biology and medicine, 2017)
Chitin nanofibers are key components in several structural biological materials. Chitin nanofibers are often part of a hierarchical structure formed by chitin molecules assembled into larger nano- and microfibers, aligned, and assembled into a twisted plywood structure. As a result, structural biological materials often couple lightweight with exceptional mechanical properties. These biological materials are an inspiration for engineered biomimetic composites that incorporate chitin nanofibers. Here, we review engineering approaches to obtain chitin nanofibers and their applications. Chitin nanofibers are the fundamental building blocks of numerous structural natural materials. From top-down to bottom-up, here we review engineering strategies to produce chitin nanofibers for engineered materials and their applications.